The emperor's caretaker. 6 - Hiiragi, Ichiha; Shoutoto, Aya (Square-Enix Manga and Books, 2026)
"Though Souren and Linhua are blissfully in love, their relationship must still be kept an absolute secret. When Linhua's powerful uncle upends everything by proposing that Linhua marry a kindhearted young man named Xuyue, she's caught entirely off guard. Sensing that something about the plan is fishy, her brother Xiuying takes action to protect his sister. With tensions rising among the Five Great Families, Linhua finds herself at the center of a conflict that could change her destiny forever!"--